Fiber-Plastic Composite Made of Old Corrugated Paper and Polyethylene (PE) with Maleic Anhydride (MAH) and Benzoyl Peroxide (BP) - Rumondang Bulan Batubara; Luthfi Hakim; Tito Sucipto (Program studi Kehutanan USU, 2013)
The research of utilizion corrugated fiber and plastic polyethylene as the raw material of making fiber plastic composite (FPC) board was useful to give solution the waste problem. The purpose of research was to evaluate physical properties (density, moisture content, water absorbtion, thickness swelling) and mechanical properties (modulus of elasticity, modulus of rupture, internal bond, screw holding power) composite board of fiber corrugated paper and comparing the use of polyethylene plastic (PE) with maleic anhydride as compatilizer and benxzoil peroxide as initiator and comparing the physical and mechanical properties FPC board wtih testing the physical and mechanical properties the composite board were carried out according to JIS A 5905-2003 hardboard S20 dan JIS A 5908 (2003) particleboards type 13.The result of the research showed that physical the fiber plastic composite board did not fulfill the standard of JIS A 5905-2003 hardboard S20, except density, water absorption and the thickness swelling. The testing of mechanical properties did not fulfill standar JIS A 5905-2003 hardboard S20 dan JIS A 5908 (2003) particleboards type 13, except internal bond and screw holding power. FPC board suitable for using exterior and interior, because by on physis and mechanical properties testing, the best value of fiber plastic composite was composition 60:40 MAH 5%. Keywords: fiber corrugated paper, polyethylene, fiber plastic composite, physiscal and mechanical properties.